Accuracy of MR Imaging in endometrial cancer: our experience - Sampath, Santhanam; Nema, Devendra; Agarwal, Raju; Lele, Prasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: MRI is a useful modality for preoperative imaging in endometrial cancer. We report our experience in Indian population managed at a tertiary care center regarding accuracy of preoperative MRI in prediction of deep myometrial invasion and cervical stromal invasion. Methods: 30 patients with endometrioid adenocarcinoma endometrium on endometrial biopsy underwent preoperative MRI in the week preceding surgery. MRI impression of depth of myometrial invasion, cervical stroma involvement and positive nodes were compared with final histopathology findings to calculate the accuracy of MRI. Results: The accuracy of MRI for estimation of tumour size was 72% and for detection of myometrial invasion was 76%. The accuracy for detection of cervical, adnexal and nodal involvement was 96%, 100% and 96% respectively. Conclusions: MRI is an accurate modality for preoperative assessment in endometrial cancer and can significantly assist in surgical planning.